SINERGI TRANSFORMATIF NILAI ISLAM DAN UNDANG-UNDANG PENDIDIKAN DALAM MENGATASI BULLYING DI MADRASAH - Muhammad Ediyani; Saifullah; Al Husaini M. Daud (Jurnal Muara Pendidikan, 2025)
Bullying in educational settings, including madrasah, is a global issue that has a significant impact on student development. Data shows that around 35% of madrasah students in Indonesia have experienced various forms of bullying, including physical, verbal, psychological, and cyberbullying. Despite the existence of national regulations, such as Law No. 20 of 2003 on the National Education System and Ministry of Education and Culture Regulation No. 82 of 2015 on the Prevention and Handling of Acts of Violence in Educational Institutions, the implementation of bullying prevention measures in madrasah has not been fully effective. On the other hand, the strengthening of Islamic values such as rahmah, ‘adl, and ihsan often remains at the normative level without being practically integrated into educational policies. This study aims to analyse the transformative synergy between Islamic values and national education regulations in efforts to prevent and address bullying in madrasah. The method used is a literature review with a descriptive-qualitative approach, through an analysis of primary sources (the Qur'an, Hadith, and national education regulations), secondary sources (scientific articles, books, and official reports), and tertiary sources (supporting documents and popular articles). The results of the study indicate that the integration of Islamic values with education regulations can produce comprehensive strategies that include: (1) moral development based on the Qur'an and Hadith, (2) anti-bullying policies based on national regulations, (3) teacher and counsellor training using an islah approach and digital literacy, and (4) strengthening the character curriculum through learning and extracurricular activities. This strategy is reinforced by a preventive approach in the form of anti-bullying campaigns based on Islamic values and collaborative student activities, as well as a curative approach through reconciliation mechanisms, educational sanctions, and psychological support for victims. This research emphasises that the transformative synergy between Islamic values and educational regulations is not only reactive but also preventive and curative in creating a safe, friendly, and Islamic-character-based madrasah ecosystem.